Extraction and Characterization of Pharmaceutical Grade Microcrystalline Cellulose From Bambara Nut (Voandzeia Subterranean (L) Thousars) Husk - E. Agboeze; N. P. Ani; E. O. Omeje (African Scientific Reports)
Microcrystalline cellulose is a vital ingredient in the food, pharmaceutical, and cosmetics industries. In this study, Bambara nutshell microcrystalline cellulose (BNS-MCC) was prepared by acid hydrolysis modification of Bambara nutshell alpha-cellulose pulp. The sample was subjected to sodium hydroxide pulping (2.0% and 17.5% NaOH respectively) and a multistage pulping treatment using 3.5% nitric acid. The analysis results showed that the pulping method was effective for substantial removal of lignin with a 14.416% yield of alpha-cellulose pulp. The organoleptic and physicochemical properties of BNS-MCC were examined. The prepared BNS-MCC powder was examined using a Scanning Electron Microscope (SEM), Fourier Transform Infrared spectroscopy (FTIR), and X-ray Diffractometer (XRD). The sample’s powder flow properties (true density, Hausner index, Carr’s index, angle of repose, powder porosity, loss on drying, and moisture sorption capacity) were (1.216g/mL, 1.34, 25.75%, 39.80o, 64.7%, and 46.81%). The results of the analysis of the BNS-MCC compared well with commercial grades and conformed to US Pharmacopeia (USP) and British Pharmacopeia specifications. This result shows that Bambara nutshells have potential application for pharmaceutical grade cellulose production used in direct compression tableting.